First report of intersex in a lutjanid: the goldband snapper Pristipomoides multidens. - Hassell, K.; Rawson, Christopher; Gagnon, Marthe Monique (Wiley-Blackwell Publishing Ltd., 2018)
This is the first report of intersex in a lutjanid species, the goldband snapper Pristipomoides multidens, in which the gonads of a male fish contain multifocal oocytes scattered among testicular tissue. The incidence rate of intersex was low (< 1.0%), with oocytes observed in the testes of only two of 206 male fish examined. The capacity for P. multidens to develop an intersex condition suggests that future monitoring of this species should include histological analysis of gonads.